2014
DOI: 10.1007/s00332-014-9199-4
|View full text |Cite
|
Sign up to set email alerts
|

Shock Waves in Dispersive Eulerian Fluids

Abstract: The long time behavior of an initial step resulting in a dispersive shock wave (DSW) for the one-dimensional isentropic Euler equations regularized by generic, third order dispersion is considered by use of Whitham averaging. Under modest assumptions, the jump conditions (DSW locus and speeds) for admissible, weak DSWs are characterized and found to depend only upon the sign of dispersion (convex or concave) and a general pressure law. Two mechanisms leading to the breakdown of this simple wave DSW theory for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 79 publications
5
67
0
Order By: Relevance
“…A positive dispersive shock, on the other hand, will produce a precursor wave train, with a linear wave edge in the upstream region and a standing soliton at the shock front. Such dispersive shock waves are solutions of the nonlinear Korteweg-de Vries equation of dispersive Eulerian fluids [Biskamp, 1973;Hoefer, 2014]. Since the fast magnetosonic oscilliton mode appears on fluid scale (see Figure 1a), our fluid model is able to capture the nonlinear trailing wave train of the thermal ion shock as we show below.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A positive dispersive shock, on the other hand, will produce a precursor wave train, with a linear wave edge in the upstream region and a standing soliton at the shock front. Such dispersive shock waves are solutions of the nonlinear Korteweg-de Vries equation of dispersive Eulerian fluids [Biskamp, 1973;Hoefer, 2014]. Since the fast magnetosonic oscilliton mode appears on fluid scale (see Figure 1a), our fluid model is able to capture the nonlinear trailing wave train of the thermal ion shock as we show below.…”
Section: Introductionmentioning
confidence: 92%
“…Note that this will give only the initial linear state of the soliton or oscilliton. The nonlinear growth rate and the full analytical solution of the oscilliton can be obtained from the nonlinear Korteweg-de Vries equation of dispersive Eulerian fluids [Biskamp, 1973;Hoefer, 2014]. The growth rate of the nonlinear low-frequency fast mode in a three-fluid model has been derived analytically by Toida and Aota [2013], and it has been shown that the low-frequency fast mode has a maximum amplitude.…”
Section: Appendix B: Derivation Of the Phase Velocity Of Solitons Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum |f m | is found by applying Newton's method to (72), resulting in the amplitude A s . Hoefer [50] obtained general results for DSW solutions for NLS equations with a general nonlinearity f (|u| 2 )u.…”
mentioning
confidence: 99%
“…More recently, Dubrovin's universality conjectures [21] introduced a new direction in the rigorous treatment of the initial stage of DSW formation. Additional progress in the understanding of solutions to the Riemann problem for non-integrable nonlinear dispersive wave equations [22,23] has made possible the analytical description of DSWs in more physically-relevant model equations.…”
mentioning
confidence: 99%